PENGARUH FAKTOR-FAKTOR MAKRO EKONOMI TERHADAP DINAMIKA PASAR MODAL DI INDONESIA - Fadilah, Mohamad Fazar; Salgangga, Selji; Maulana, Sofyan Septian; Kusumaningtyas, Alissa; Hamdani, Irfan; Laelani, Ade Yosi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
Focusing on understanding the conditions of the Indonesian stock market (IHSG), this study examines the influence of macroeconomic elements such as interest rates, inflation, and exchange rates. The sample for this analysis was selected using purposive sampling methods. A quantitative approach was applied in this analysis, and data sources were obtained from various official institutions, including the Central Bank of Indonesia and the Indonesia Stock Exchange. The data analysis, using multiple linear regression, indicates that inflation and exchange rates partially impact IHSG, while interest rates do not. Each macroeconomic component such as interest rates, inflation, and exchange rates has been found to have a significant collective impact on IHSG